How to improve at swimming - Mason, Paul (Kent, England Ticktock Entertainment Ltd., 2005)
How to improve at swimming does not promise instant success. It simply gives you the know-how to become the best at whatever you choose to do
Introduction -- Know the sport -- The strokes -- Starts and turns -- Be fit, stay fit -- Race tactics & events -- Swimming in other sports -- Safety -- How the famous do it -- Glossary -- Index
"This edition is printed in 2008 exclusively for WS Pacific Publication, Inc., Manila Philippines" - copyright page
Keywords: Swimming